Optimizing maintenance scheduling of water distribution pumps using Reliability Centered Maintenance (RCM) - Achmad Muhazir; Mohammad Adam Jerusalem (Jurnal Polimesin, 2026)
Water distribution pump systems are critical assets in public utility services, where failures can directly disrupt service continuity and increase operational costs. Empirical evidence from water utility operations indicates that conventional maintenance strategies are often unable to effectively control downtime and reliability degradation. This study aims to analyze maintenance scheduling for water distribution pumps using the Reliability Centered Maintenance (RCM) approach to improve system reliability and availability. A quantitative case study was conducted at a regional water utility company using one-year historical operational and maintenance data from January to December 2025. The research methodology integrates Pareto analysis to identify critical assets, Failure Mode and Effect Analysis (FMEA) to prioritize dominant failure modes, and reliability analysis based on the Weibull distribution to estimate Mean Time To Failure (MTTF) and Mean Time To Repair (MTTR). The RCM Decision Worksheet was applied to determine appropriate maintenance actions and optimal preventive replacement intervals. The results show that the distribution pump is the most critical asset, contributing the highest downtime (620 hours per year across 11 failures), with an MTTF of 1,683 hours and an MTTR of 4.74 hours. The optimal preventive replacement interval was identified at 1,450 operating hours, reducing annual downtime to 127.1 hours (79.5% reduction) and increasing system availability to 99.793%. These findings confirm that RCM-based maintenance scheduling significantly enhances reliability, availability, and operational performance of water distribution pump systems, providing practical guidance for maintenance optimization in water utility industries.